Targeted Next-Generation Sequencing Reveals Mutations in Non-coding Regions and Potential Regulatory Sequences of Calpain-3 Gene in Polish Limb–Girdle Muscular Dystrophy Patients - Macias, Anna; Fichna, Jakub Piotr; Topolewska, Malgorzata; Rȩdowicz, Maria J.; Kaminska, Anna M.; Kostera-Pruszczyk, Anna (Frontiers in Neuroscience, 2021)
Limb-girdle muscular dystrophy type R1 (LGMDR1) is caused by mutations in CAPN3 and is the most common type of recessive LGMD. Even with the use of whole exome sequencing (WES) only one mutant allele of CAPN3 is found in significant number of LGMDR patients. This points to a role of non-coding, intronic or regulatory, sequence variants in the disease pathogenesis. Targeted sequencing of the whole CAPN3 gene including not only intronic, 3’ and 5’ UTRs, but also potential regulatory regions was performed in 27 patients suspected with LGMDR1. This group included 13 patients with only one mutated CAPN3 allele detected previously with exome sequencing. A second rare variant in the non-coding part of CAPN3 was found in 11 of 13 patients with previously identified single mutation. Intronic mutations were found in ten cases, with c.1746-20C>G variant present in seven patients. In addition, a large deletion of exons 2-8 was found in one patient. In the patients with no causative mutation previously found, we detected rare CAPN3 variants in five out of ten patients, and in two of them in a compound heterozygous state. Rare variants within putative regulatory sequences distant from the CAPN3 gene were found in 15 patients, although in 11 of these cases other variants are deemed causative. The results indicate that intronic mutations are common in Polish LGMDR patients and testing for non-coding mutations in CAPN3 should be performed in apparently single heterozygous patients.